2005
DOI: 10.1051/0004-6361:20053508
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen dissociation of naphthalene cations: a theoretical study

Abstract: We present the computational results of removing mono and di-hydrogen atoms from the naphthalene cation. Calculations are performed at the B3LYP level with an extended basis. Two channels are studied, -H and -H 2 , and these processes are discussed within the frame of photodissociation of PAHs in the interstellar medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 26 publications
5
34
0
Order By: Relevance
“…22,23 For the neutral molecule, comparable values are obtained with only a different ordering between the two fragments. 34,35,44 The energy difference is predicted to be 0.07 eV between the two channels.…”
Section: Dft Calculationsmentioning
confidence: 71%
“…22,23 For the neutral molecule, comparable values are obtained with only a different ordering between the two fragments. 34,35,44 The energy difference is predicted to be 0.07 eV between the two channels.…”
Section: Dft Calculationsmentioning
confidence: 71%
“…It is also possible that the cations could lose a hydrogen atom to improve the C-C bonding. The loss of an H atom for a PAH cation was found (Jolibois et al 2005) to be favored over the loss of H 2 , and we suspect this will also be true for the diamondoids.…”
Section: Diamondoid Cation Vibrational Spectroscopymentioning
confidence: 87%
“…This 1,2-hydrogen (or deuterium) shift is a well-known phenomenon in organic chemistry (Whitmore 1932;Kuck 2002;Bruice 2014), and specifically for reactions in aromatic molecules (Brooks & Scott 1999). Furthermore, in theoretical studies of PAH species, the 1,2-H shift across the PAH rim has been shown to occur once they are excited to internal energies above 1 eV, leading to the formation of various intermediate isomers containing a C -HH group (Jolibois et al 2005;Trinquier et al 2017;Castellanos et al 2018b). Using DFT, we calculated the potential energy reaction pathway for D migration along [H -C 14 D 10 ] + , and the results are depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%